Environmental damage in the General Environmental Law - Lanegra Quispe, Ivan (2013)
This paper looks at environmental damage definition stipulated by Peruvian General Environmental Law as well as its implications for the environmental policy development. It also outlines complexities involved identifying environmental damage as much as designing and implementing public policies according to Peruvian legislation processing.